Epidemiology of human visceral leishmaniasis in Petrolina, Pernambuco, from 2009 to 2020: a descriptive analysis - Silva, Márcia Marília de Souza (2021)
Introduction: Visceral Leishmaniasis (VL) is classified as a neglected tropical disease caused by the genus Leishmania, which has as vector the sand fly insect of the genus Lutzomyia. The northeast region of Brazil still has the highest number of cases, and the municipality of Petrolina, located in the inland of the state of Pernambuco, registers all new cases. Thus, the objective of the study described the epidemiological characteristics of cases of visceral leishmaniasis in Petrolina from 2009 to 2020. Methods: The survey was carried out based on information available in the available database of the Information System for Diseases of Notification and in the Health Department of the municipality of Petrolina. Epidemiological indicators were calculated and, for this, data referring to sex, age group, race, area of residence, case evolution, confirmation criteria, and HIV co-infection were used. Results: In the period studied, 354 cases were confirmed with a treatment coefficient higher than the national average. In addition, the disease was observed predominantly in males, brown race, in non-residents in the urban area of the city, and during childhood. Conclusions: The data available in the databases still have flaws. A lack of complete information in the notification forms leads to failure in investigating the disease and, consequently, an underestimated incidence. Thus, the results obtained contribute to a better understanding of the current scenario of leishmaniasis in the city of Petrolina-PE.